Alluvial Fans in Southern Iran Geological, Environmental and Remote Sensing Analyses - Pourmorad, Saeid; Mohanty, Ashutosh (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book presents a complete set of studies of alluvial fan sediments in southern Iran from the point of view of sedimentology, sedimentary geochemistry, tectonics, economic geology, groundwater, geomorphology, hazards and telemetry. In addition, the book focuses on advanced topics and theory, which practically serves as a model for the study of this type of sediment around the world. Alluvial fans are an important and fundamental factor in many sciences such as geology, environmental science, natural hazards, groundwater science, agriculture and many other related sciences. Lack of accurate knowledge of their constituent sediments has always been an important problem for experts in many science disciplines. From the economic point of view, the identification of alluvial fan deposits is of particular importance. For example, alluvial deposits are the centre of groundwater accumulation, and most groundwater reservoirs within the sedimentary basin are fed by water from alluvial deposits. Most of the gold production in South Africa has been formed as placer deposits in ancient alluvial fans. In addition, a large amount of uranium placer deposits is extracted from old alluvial fans in sedimentary basins in South Africa. This book serves as an ideal guide for experts in earth and environmental sciences and hydrology.
Introduction -- Geology of the study area -- Advanced sedimentology studies -- Petrographic and geochemical studies -- Tectonic and morphotectonic studies -- Environmental geological studies -- Remote sensing studies -- Basin analysis and modeling. .
Keywords: Physical geography; Sedimentology; Petrology; Geochemistry; Geology; Physical Geography; Sedimentology; Petrology; Geochemistry; Geology